ผืนผ้า อาภรณ์บาติกแด่ผู้ล่วงลับ - ฤทัยทิพย์ รัตนพันธ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
In the past, I used to fulfill the wish of a dying person who wished to wear batik outfits in theirfuneral. I fulfilled such a wish by painting a piece of black and white batik fabric for that person. That experience inspires this thesis work of the “Batik Clothing for the Deceased. ” project. The objective of this project is to create batik fabric with dark tone colours for the dead. The fabric is delicately and beautifully designed in order to pay homage to the dead. Delicate motifs that represent good meanings are drawn on the fabric which is presented in the form of installation art comprised of 3 pieces of batik fabric, outfits, and feet and coffin covers. This set of batik fabric utensils are used in the environs with dim light. They cover the things that are believed to be the last things that the dead will take along with them to the after death. I analyzed the overall concept, compositions, tones and outcomes of this project in order to understand how to use symbols to represent all the concepts and ideas of the works in this project. The objective and overall concept of this project are accomplished because the created fabric expresses the delicate feelings that I have towards the dead. Creating the works in this project, I discovered the dying technique that can be used for creating the colour gradation impact is to dye the batik fabric over and over again at least three times. This technique enables the fabric to deliver the feelings from its creator and owner to the dead